Challenges and confrontations for the clinical practice of nurses: Scoping review (Research, Society and Development, 2022)
Objective: To identify the challenges and potential for nurses' clinical practice in primary health care in the face of COVID-19. Method: Scoping Review, according to Joanna Briggs Institute (JBI), with the guiding question: “What are the challenges and potential of nurses' clinical practice in primary health care in the face of COVID-19?”. Including national and international studies in English, Portuguese and Spanish, from 2019 to 2022, with searches in four databases. Results: 9089 articles were found, and eight were selected as the final sample. The studies highlighted some of the challenges concerning COVID-19, such as the excessive working hours of nurses, lack of continuing education, insufficient Personal Protective Equipment (PPE), and underfunding of PHC, among others, as well as the potential, such as the adaptability and workforce of health professionals, especially nurses. Conclusions: It was evidenced that the challenges for the clinical practice of nurses in the face of COVID-19 are in facing and overcoming structural, economic, social and emotional issues generated by situations such as the lack of equipment and materials and working with the unknown. The potential is related to the possibilities of developing clinical competencies and the adaptability of the workforce to serve people with safety and quality.